In vitro cultivation of petals of four varieties of Begonia elatior - Velasco Martínez, Fernanda; González Rosas, Héctor; Castillo González, Ana María; Gaytán Acuña, Elda Aracely (Revista Mexicana de Ciencias Agrícolas, 2018)
This investigation was carried out with the objective of establishing the protocol to know the totipotencia of the petal for the generation of seedling massively by means of the addition, to the culture medium, of an auxin and a cytokinin and to induce the cloning of four varieties of Begonia elatior. Full petals were used that were grown in Murashige and Skoog culture medium in a completely randomized experimental design consisting of five combined levels of ANA and BA (0, 1, 0.5, 2 and 3 mg L-1). The highest regeneration of callus recorded, on average, 57.2%, in petals of the cv ‘Heidi’ and 46.4% in the variety ‘Gloriosa’. These results were given at 65 days of MS medium culture supplemented with 1 mg L-1 of ANA and 1 mg L-1 of BA. The best sprout formation and growth was obtained with MS medium added with 1 mg L-1 of ANA and 1 mg L-1 of BA with 13.2% in the variety ‘Heidi’ and ‘Gloriosa’. Occasionally, floral buds were present in the treatment 1 mg L-1 of ANA + 1 mg L-1 of BA in the cv ‘Heidi’. The root formation was obtained only in the ‘Heidi’ variety and 1 mg L-1 of ANA + 1 mg L-1 of BA was induced in the treatment. It is possible to obtain seedlings from petals of Begonia elatior.